Obesity and the Emergency Short Stay Unit. (January 2017) - Marquez, Marc; McGuiness, William; Cross, Rachel; Mitra, Biswadev
Highlights: Obesity was not associated with increased length of stay in ESSU. There was no association between obesity and increased rates of hospital admission. Obese patients had significantly higher allied health interventions required. The proportion of plain X-rays performed was significantly more among obese patients. Abstract: Objectives: To evaluate the health service requirements of obese patients admitted to an Emergency Short Stay Unit (ESSU) and specifically compare length of stay (LOS), failure of ESSU management, and rates of investigations and allied health interventions among obese and non-obese patients. Methods: A prospective cohort study, using convenience sampling was conducted. The body mass index (BMI) of participants was calculated and those with a BMI of ⩾30 were allocated to the obese group, and those that had a BMI of <30 to the non-obese group. Data collected included demographics, admission diagnosis, time and date of ESSU admission and discharge, discharge disposition, radiological investigations, and referrals made to allied health personnel during ESSU admission. Results: There were 262 patients that were recruited sub-grouped into 127 (48.5%) obese participants and 135 (51.5%) non-obese participants with similar sex and diagnostic category distributions. The mean LOS in ESSU was similar – 11.5 h (95% CI: 9.9–13.1) for obese patients and, 10.2 h (95% CI: 8.8–11.6) for non-obese patients (p = 0.21). Failure rates of ESSU management, defined as inpatient admission to hospital, were also similar with 29 (22.8%) obese patients admitted to hospital compared to 25 (18.5%) non-obese patients (p = 0.39). Plain X-ray requests were significantly higher among obese patients (71.6 vs 53.3%; p = 0.002), as was the rate of allied health interventions (p = 0.001). Conclusion: There was no significant difference in inpatient admission rates or LOS between obese and non-obese patients managed in the ESSU. Provisions for increased rate of investigations and allied health interventions for obese patients may facilitate timely assessment and disposition from ESSU.